PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP ELEMEN-ELEMEN INTEGRATED REPORTING (Studi Pada Perusahaan Non-Keuangan yang listing di BEI Tahun 2015) - Novaridha, Ira Astria; Indrawati, Novita; ', Al-Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research is aimed to examine and analyze influence of institutional ownership, firm size and profitability on the elements of integrated reporting in the annual report non-financial companies listed on the Indonesia Stock Exchange in 2015. Sample data is using simple random sampling methode to the non-financial companies that listed in Indonesian Stock Exchange during 2015. The number of companies taken as samples in this study covers about 85 company annual reports. This study uses content analysis to measure elements of integrated reporting in the annual report. Processing and analysis of data using multiple regression with SPSS v22. The result of this research showed those independent variables of institutional ownership, size and profitability does not affect the elements of integrated reporting in the annual report non-financial companies listed on the Indonesia Stock Exchange in 2015.Keyword: institutional ownership, firm size , profitability and elements of integrated reporting